Hoax Distribution in Social Media After Ratification of Omnibus Law - Febriansyah Febriansyah; Nani Nurani Muksin (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2021)
Social media had both positive and negative impacts. Lately, hoaxes had spread on social media massively after the ratification of the Job Creation Law (Omnibus Law). This research aimed to obtain an overview of hoax distribution on social media that emerged after the ratification of the Job Creation Law, find out the factors that cause it, and solve hoaxes on social media. The research method used was a descriptive qualitative approach. The results showed that hoax contents were circulating on social media after the ratification of the Job Creation Law. This was due to the lack of awareness of the digital media literacy culture and the absence of clarity regarding the draft of the Job Creation bill that was passed. The solution to eradicating hoaxes on social media could be done with three approaches: culture (literacy), technology, and law.